Green Synthesis of Cobalt Oxide Nanoparticles (Co3O4 NPs) using Bauhinia Racemosa (Thiruvachi) Leaves Extract and Its antioxidant, anti-diabetic, and Anti-inflammatory Properties - Vanitha, G.; Manikandan, R.; Prakasam, A.; Navinkumar, M. D.; Sathiyamoorthi, K.; Dhinakaran, B. (Journal of Scientific Research, 2023)
This study aims to appraise the antioxidant, anti-diabetic, and anti-inflammatory accomplishments of green synthesized cobalt oxide nanoparticles (Co3O4 NPs) mediated by Bauhinia racemosa leaves. Bauhinia racemosa is commonly called ''Thiruvachi' leaf tree in Tamil. The green synthesized Co3O4 NPs are calcinated at 350 °C, then characterized by TG/DTA, UV, FTIR, FL, XRD, DLS, SEM with EDS analysis, TEM, and Supercapacitor performance studies with CV analysis. TGA/DTA result associated with weight loss and exothermic reaction due to desorption of chemisorbed water. FTIR was performed to identify the functional groups of carbonyl, hydroxyl, amine, and protein molecules, which form a layer covering Co3O4 NPs and stabilize the Co3O4 NPs in the medium. The XRD pattern peaks are associated with a poly cubic crystalline form of metallic cobalt oxide nanoparticles. The average grain size of Co3O4 NPs is 36.45 nm. This research focused on Biological studies like antioxidant, anti-diabetic, and anti-inflammatory, total antioxidant measured by phosphomolyptenium reagent with vitamin C as the standard, Anti-diabetics studies carried out by α-amylase inhibition method and anti-inflammatory bustle followed by BSA denaturation technique. The spectral and morphological data confirms the Co3O4 NPs formation. The anti-inflammatory activity showed good results than the antioxidant and anti-diabetic activity.